Answer:
A
Step-by-step explanation:
Discriminant= 8^2-4(16)(1)
=0
There are an infinite number of possibilities, and not enough information
to decide which possibility is really the one inside the function machine.
Here are a few. Each of these gives the result that you described,
and there are an infinite number of others:
f(x) = x
f(x) = 2x + 1
f(x) = 10x + 9
f(x) = x² - 2
f(x) = 7x² - 8
f(x) = 31x³ + 30
f(x) = log( |x| ) - 1
f(x) = ln( |x| ) - 1
f(x) = x tan(45°)
.
.
etc.
Answer:
Step-by-step explanation:
243+94+b=360
b=360-337
=23
Answer:
a=2
Step-by-step explanation:
Firstly, in order to simplify the expression, we should aim to combine the two terms given. In order to do this, both must have the same denominator. We can give them the same denominator by multiplying the second term
by
. This way the fraction value remains the same but now has the same denominator as the first term:
![-\frac{2}{x+2} *\frac{x+2}{x+2} \\\\=\frac{(-2)(x+2)}{(x+2)(x+2)} \\\\=\frac{-2x-4}{(x+2)^{2}}](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7Bx%2B2%7D%20%2A%5Cfrac%7Bx%2B2%7D%7Bx%2B2%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B%28-2%29%28x%2B2%29%7D%7B%28x%2B2%29%28x%2B2%29%7D%20%5C%5C%5C%5C%3D%5Cfrac%7B-2x-4%7D%7B%28x%2B2%29%5E%7B2%7D%7D)
From here we can now combine the two terms:
![\frac{2x+6}{(x+2)^{2}} +\frac{-2x-4}{(x+2)^{2}} \\\\= \frac{(2x+6)+(-2x-4)}{(x+2)^{2}} \\\\\\=\frac{2x+6-2x-4}{(x+2)^{2}}\\\\= \frac{2}{(x+2)^{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%2B6%7D%7B%28x%2B2%29%5E%7B2%7D%7D%20%2B%5Cfrac%7B-2x-4%7D%7B%28x%2B2%29%5E%7B2%7D%7D%20%5C%5C%5C%5C%3D%20%5Cfrac%7B%282x%2B6%29%2B%28-2x-4%29%7D%7B%28x%2B2%29%5E%7B2%7D%7D%20%5C%5C%5C%5C%5C%5C%3D%5Cfrac%7B2x%2B6-2x-4%7D%7B%28x%2B2%29%5E%7B2%7D%7D%5C%5C%5C%5C%3D%20%5Cfrac%7B2%7D%7B%28x%2B2%29%5E%7B2%7D%7D)
Therefore, a = 2.
Hope this helped!